KORELASI ANTAR BOBOT BADAN TERHADAP KUANTITAS DAN KUALITAS SEMEN SEGAR SAPI BALI DI BALAI BESAR INSEMINASI BUATAN (BBIB) SINGOSARI KABUPATEN MALANG - agustina widyasworo; Yuhanin Zamrodah; Elsa Nanda Sari Elsa Nanda Sari (AVES: Jurnal Ilmu Peternakan, 2023)
The purpose of this study was to determine the correlation of body weight on fresh semen production of Bali cattle conducted at BBIB Singosari, Toyomarto Village. The research was conducted from 6 June to 13 June 2023. The method used was a survey using semen data for Bali cattle from different bulls and body weight which were grouped into three categories. The data analysis used a one-way test with observed variables such as body weight, semen volume, semen motility, semen abnormalities, and semen concentration. The results of this study mean the body weight of Bali cattle is 502.575 kg, 560.85 kg, 609.9 kg. The average yield of semen volume was 6.31 ml, 5.87 ml and 5.92 ml. The average yield of motility was 69.28%, 73.09%, 67.09%. The average abnormality results were 7.79%, 14.27%, 9.51%. Based on the results of this study it can be concluded that there is no correlation with semen volume, semen motility, semen abnormalities, and semen concentration.